How to involve rural NEET youths in agriculture? Highlights of an untold story. Issue 5 (20th October 2018) - Simões, Francisco
ABSTRACT: This article discusses how to involve rural youths not in employment, education, or training (or NEETs) in agriculture. A Portuguese network-based project called Terra Nostra, carried out from 2013 to 2015 to engage and train NEETs in ecoagriculture activities, was examined to address this issue. The study focused on three aspects: a reanalysis of Terra Nostra 's final report, based on the bioecological model, targeting typical problems with NEETs' involvement and how the project aimed to overcome them; the lessons learned from the project according to the literature; and the state of the art regarding identical social interventions with NEETs in Portugal and the rest of Europe. A major conclusion stemming from the analysis is that similar projects will need to address the limitations of employment public services in reaching out to rural NEETs and the state's excessive protectionism of the sector.